Trends in Mortality in an Australian Tertiary Surgical Neonatal Intensive Care Unit - Joseph Kiran Tauro; Karen Walker; Robert Halliday; Vishal Jatana; Amit Trivedi (EL-Med-Pub, 2018)
Aim: The aim of the study was to estimate mortality rate and trend in the neonate admitted to a surgical neonatal intensive care unit. Methods: This study was a retrospective cohort analysis of all neonatal (from birth to Results: There were a total of 8994 admissions with 425 deaths during the study period, of whom 328 infants met inclusion criteria. In this group 18.9% (n=62) were admitted for a surgical condition, 35.4% (n=116) for cardiac disease and 45.7% (n=150) for other reasons. The median birth weight was 2715g (IQR 1890g-3220g) and the median gestational age was 37 weeks (IQR 33-39 weeks). The inter-quartile range for length of stay was between 2 to 20 days. The overall mortality rate was 3.6% over 16 years. There was a decline in mortality rate from 5.9% in 2000 to 3.5% in 2015 (p=0.06). Female infants accounted for 41% of the deaths. On multivariate analysis only very low birth weight was an independent predictor of mortality for surgical and cardiac deaths compared to deaths by other cause. Conclusions: There has been an overall decline in mortality in the surgical neonatal population from 2000 to 2015.